Unveiling Shadows: Tracking Youth Disengagement from the Church [Menyingkap Bayangan: Melacak Penyebab Keterpisahan Kaum Muda dari Gereja] - Samuel Ntsanwisi (Diligentia: Journal of Theology and Christian Education, 2024)
This study examines the waning attendance in youth ministry within rural and township areas of South Africa's "mainline churches" and its potential implications for youth development. Amidst prevailing challenges like substance abuse, adolescent pregnancy, and mental health concerns, the church, often a crucial source of guidance, has the potential to offer significant support. However, changing cultural dynamics, modernization, socio-economic influences, the challenges posed by urbanization, and the intersecting issues of LGBTQ inclusivity, disability considerations, and evolving identity dynamics, along with alternative entertainment, have collectively contributed to youth disengagement from conventional religious practices. This decline raises substantial concerns regarding its impact on the youth’s moral and spiritual well-being. Through a comprehensive literature review, this research aims to understand the underlying causes of this decline and propose strategies for revitalising the youth ministry. By metaphorically "illuminating the hidden obstacles," this study seeks to empower the church to foster spiritual growth, influence South Africa's youth positively, and address pressing challenges effectively.